Raj - Mehta, Gita (London Jonathan Cape, 1989)
Jaya Singh is the intelligent, beautiful, and compassionate daughter of the Maharajah and Maharani of Balmer. Raised in the thousand-year-old tradition of purdah, a strict regime of seclusion, silence, and submission, Jaya is ill-prepared to assume the role of Regent Maharani of Sirpur upon the death of her decadent, Westernized husband. But Jaya bravely fulfills her duty and soon finds herself thrust into the center of a roiling political battle in which the future of the kingdom is at stake . . . and her own future as well.
Keywords: India -- British Occupation of India (1765-1947) -- Royal Houses -- Social Change